2022
DOI: 10.1002/glia.24307
|View full text |Cite
|
Sign up to set email alerts
|

EphA4/ephrinA3 reverse signaling mediated downregulation of glutamate transporter GLAST in Müller cells in an experimental glaucoma model

Abstract: Deficiency of glutamate transporter GLAST in Müller cells may be culpable for excessive extracellular glutamate, which involves in retinal ganglion cell (RGC) damage in glaucoma. We elucidated how GLAST was regulated in rat chronic ocular hypertension (COH) model. Western blot and whole-cell patch-clamp recordings showed that GLAST proteins and GLAST-mediated current densities in Müller cells were downregulated at the early stages of COH. In normal rats, intravitreal injection of the ephrinA3 activator EphA4-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Inflammatory responses have been identified as crucial in the pathogenesis of neurodegenerative diseases 44–46 . Retinal injury triggers the activation of vascular inflammation and glial cells, including microglia, astrocytes, and Müller cells 23,47 . To explore whether oral melatonin supplementation can affect retinal inflammation in EAAC1 −/− mice, we conducted immunofluorescence staining using antibodies against CD45, Iba1/CD68, GFAP, and vimentin, which are markers of leukocytes, microglia/macrophages and their activated form, astrocytes, and Müller cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory responses have been identified as crucial in the pathogenesis of neurodegenerative diseases 44–46 . Retinal injury triggers the activation of vascular inflammation and glial cells, including microglia, astrocytes, and Müller cells 23,47 . To explore whether oral melatonin supplementation can affect retinal inflammation in EAAC1 −/− mice, we conducted immunofluorescence staining using antibodies against CD45, Iba1/CD68, GFAP, and vimentin, which are markers of leukocytes, microglia/macrophages and their activated form, astrocytes, and Müller cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46] Retinal injury triggers the activation of vascular inflammation and glial cells, including microglia, astrocytes, and Müller cells. 23,47 To explore whether oral melatonin supplementation can affect retinal inflammation in EAAC1 −/− mice, we conducted immunofluorescence staining using antibodies against CD45, Iba1/CD68, GFAP, and vimentin, which are markers of leukocytes, microglia/macrophages and their activated form, astrocytes, and Müller cells, respectively. Our data showed a noteworthy rise in CD45-positive cells as well as Iba1/ CD68 double-positive cells among EAAC1 −/− mice, indicating activation of inflammatory responses, and melatonin administration effectively alleviated these inflammatory responses (Figure 7A-D).…”
Section: Melatonin Alleviated the Inflammatory Response In Eaac1 −/− ...mentioning
confidence: 99%
“…In addition, it has been demonstrated that reduced expression of EphrinA3 activated the PI3K/Akt pathway in the glaucoma model (Zhou et al, 2023) and the miR-204-5p/EphA4 axis activated the PI3K/AKT pathway, ameliorating neurological injury in ischemic stroke (Shi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that the Ephrin ligand and Eph receptor system regulate a number of physiological and pathological processes that may be engaged in the pathological process of cerebral ischemic damage (Goldshmit et al., 2011; Li et al., 2012; Yang et al., 2014). In addition, it has been demonstrated that reduced expression of EphrinA3 activated the PI3K/Akt pathway in the glaucoma model (Zhou et al., 2023) and the miR‐204‐5p/EphA4 axis activated the PI3K/AKT pathway, ameliorating neurological injury in ischemic stroke (Shi et al., 2023).…”
Section: Introductionmentioning
confidence: 99%